Feeding Habits of Medical Students - P. I. Melnichenko; N. A. Ermakova; S. A. Mishina; V. A. Frolova; A. Sorokova (Сеченовский вестник, 2022)
One of the most important components of students' health is a balanced diet. Features lifestyle of students, characterized by a defi cit of the consolidated time high pace of life, a large overvoltage of the nervous system, lead to violations of the regime, the nature and conditions of supply. This is a risk factor for many diseases. In this regard, the aim of the work was to evaluate the characteristics of the nutrition of students aff ecting their health. As a result of the research it has been found that a signifi cant part of the students are fed at least three times a day. The mean values of body mass index in men determined at the upper limit and a substantial portion of them are marked symptoms of hypertension. Most non-diet relationship established with gastrointestinal disease, symptoms of overweight and functional disorders of the endocrine system.